Arbuscular mycorrhizal fungal effects on plant competition and community structure. (15th June 2015) - Lin, Guigang; McCormack, M. Luke; Guo, Dali; Phillips, Ryan
Summary Arbuscular mycorrhizal fungi (AMF) mediate plant interspecific competition and community structure. However, the magnitude and direction of AMF effects and underlying mechanisms are not clear. Here, we synthesized the results of 304 studies to evaluate how AMF affect plant competition and community structure and which abiotic and biotic conditions in experimental design modify these AMF effects. The magnitude and direction of AMF effects on plant competitive ability (in terms of competitive response) differed markedly among plant functional groups. When AMF inoculum was added, competitive ability was strongly enhanced in N‐fixing forbs and was significantly suppressed in C3 grasses, whereas no effect was observed in C4 grasses, non‐N‐fixing forbs and woody species. Furthermore, AMF inoculation increased competitive ability of perennial species when their competitors were annual species. AMF inoculation differentially influenced separate aspects of plant community structure and species composition. AMF inoculation significantly increased plant diversity but had no effects on plant productivity. Response of dominant plant species to AMF inoculation was the determining factor in explaining variations in how and to what degree plant diversity was influenced by AMF inoculation. When dominant species derived strong benefits from AMF, their dominance level was increased by AMF inoculation, which consequently decreased plant diversity. We did not find stronger AMF effects on plant diversity and productivity when greater numbers of AMF species were used in the inoculation. Synthesis. Despite large variations in AMF effects among studies, a unifying mechanism was observed that the mycorrhizal responsiveness (differences in plant growth between AMF and non‐AMF colonization treatments) of target and neighbouring plant species can determine AMF effects on the competitive outcome among plant species, which in turn influenced plant species diversity and community composition. Given that plant traits, soil nutrient conditions and probably mycorrhizal fungal traits are all factors determining the degree of mycorrhizal response of plant species, future studies should explicitly consider each of these factors in experimental design to better understand AMF effects on plant coexistence, plant community dynamics and ecosystem processes.